Построение архитектуры активной информационной системы интеллектуальных многоцелевых транспортных средств - Никонов, О. Я. (НТУ "ХПИ", 2010)
Розглянута задача побудови архітектури активної інформаційної системи інтелектуальних багатоцільових транспортних засобів підвищеної прохідності на основі новітніх інформаційних і супутникових технологій.

The problem of construction of active information system architecture of intellectual multi-purpose vehicles of a cross-country capacity on the basis of the newest information and satellite technologies is considered.
Keywords: автомобильный транспорт; обеспечение безопасности; прием информации; передача информации; мониторинг; транспортная информация; информационные технологии; спутниковые технологии